Benang Kusut Pemulihan Jankis di Makassar - Nurul Ilmi Idrus (Universitas Muslim Maros, 2019)
Drug abuse has become one of the major problems in Indonesia, including in South Sulawesi. Many of them are criminalized, but prisons do not provide a deterrent effect, both for drug users and drug dealers because it is no secret, prison is a fertile land for drug trading and drug trafficking. Apart from that, even though the spirit of rehabilitation was strongly proclaimed by the government, drug user were jailed more than rehabilitated, so they were identified as criminals than as victims who need rehabilitation. While the many existing literatures deal with rehabilitation, little (if any) concerns with the dynamics of recovery process. This article fills this gap. The study was conducted in Makassar, the capital city of South Sulawesi. Thirty-two informants participated in the study, consisting of twenty jankis, five jankis’ mothers and five jankis’wives/girlfriends and an activist. Data was collected using in-depth interview. The study shows that lack of understanding of the complexity of the problems associated with jankis causes people to easily stigmatize and ignore them. Whereas instead of perceiving jankis as criminals, they are victims of the chain of drug trafficking, unless one is a drug dealer. In a recovery effort, even though medical rehabilitation is important, social rehabilitation is very significant and this involves close relatives, especially women such as mothers/wives/girlfriends. In the recovery process, not only junkis are